Chondroitin 6-Sulfate as a Novel Biomarker for Mucopolysaccharidosis IVA and VII - Shimada, Tsutomu (JIMD Rep, 2014)
Chondroitin 6-sulfate (C6S), a glycosaminoglycan (GAG), is distributed mainly in the growth plates, aorta, and cornea; however, the physiological function of C6S is not fully understood. One of the limitations is that no rapid, accurate quantitative method to measure C6S has been established. Mucopolysaccharidosis IVA and VII (MPS IVA and VII) are caused by the deficiency of N-acetylgalactosamine-6-sulfate sulfatase and β-d-glucuronidase, respectively, resulting in accumulation of C6S and other GAG(s). While levels of keratan sulfate (KS), heparan sulfate, and dermatan sulfate in samples from MPS patients are well described, this is the first report of quantitative analysis of C6S levels in samples from MPS IVA and VII patients. We developed a method to digest polymeric C6S and measure resultant disaccharides using liquid chromatography–tandem mass spectrometry (LC-MS/MS). C6S levels were measured in the blood from control subjects and patients with MPS IVA and VII aged from 0 to 58 years of age. We also assayed KS levels in the same samples for comparison with C6S. Levels of C6S in the blood decreased with age and were significantly elevated in patients with MPS IVA and VII, compared with age-matched controls. Levels of KS in patients with MPS IVA were also higher than those in age-matched controls, although differences were less pronounced than with C6S. Combining KS and C6S data, discriminated patients with MPS IVA from age-matched control subjects were better than either C6S or KS levels alone. In conclusion, this first report showing that blood levels of C6S are quantitatively evaluated in patients with MPS IVA and VII indicates that C6S could be a useful biomarker for these metabolic disorders.